Antioxidant Biomolecules and Their Potential for the Treatment of Difficult-to-Treat Depression and Conventional Treatment-Resistant Depression - María Eugenia Riveros; Alba Ávila; Koen Schruers; Fernando Ezquer (MDPI AG, 2022)
Major depression is a devastating disease affecting an increasing number of people from a young age worldwide, a situation that is expected to be worsened by the COVID-19 pandemic. New approaches for the treatment of this disease are urgently needed since available treatments are not effective for all patients, take a long time to produce an effect, and are not well-tolerated in many cases; moreover, they are not safe for all patients. There is solid evidence showing that the antioxidant capacity is lower and the oxidative damage is higher in the brains of depressed patients as compared with healthy controls. Mitochondrial disfunction is associated with depression and other neuropsychiatric disorders, and this dysfunction can be an important source of oxidative damage. Additionally, neuroinflammation that is commonly present in the brain of depressive patients highly contributes to the generation of reactive oxygen species (ROS). There is evidence showing that pro-inflammatory diets can increase depression risk; on the contrary, an anti-inflammatory diet such as the Mediterranean diet can decrease it. Therefore, it is interesting to evaluate the possible role of plant-derived antioxidants in depression treatment and prevention as well as other biomolecules with high antioxidant and anti-inflammatory potential such as the molecules paracrinely secreted by mesenchymal stem cells. In this review, we evaluated the preclinical and clinical evidence showing the potential effects of different antioxidant and anti-inflammatory biomolecules as antidepressants, with a focus on difficult-to-treat depression and conventional treatment-resistant depression.